Implementation of Talent-Based Projects as a Differentiated Learning Strategy to Optimize the Potential of 8th-Grade Students at SMP Alam Azzahra, Way Jepara, East Lampung - Putri Khoirunnisa; Laila Nursafitri (CV. Edujavare Publishing, 2026)
This study aims to analyze the application of talent-based projects as a differentiated learning strategy to optimize the potential of eighth-grade students at SMP Alam Azzahra Way Jepara Lampung Timur. The research background is based on the need to meet the diverse learning needs of students, which are often not accommodated in a uniform classical learning model. In the research that will be carried out, the researcher has the aim of explaining and analyzing the implementation of talent-based projects asa differentiated learning strategy to optimize student potential. The In this research, the researcher employs a qualitative approach using a field-based case study method. The participants composed of teachers and students involved in the implementation of talent-based projects. Data were collected through observation, in-depth interviews, and document analysis, then analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that talent-based projects provide opportunities for students to develop their abilities according to their interests and strengths. This strategy enhances student engagement, fosters creativity, strengthens independent learning, and increases self-confidence in presenting learning outcomes. Furthermore, teachers act as facilitators who guide students in designing and completing projects based on their individual characteristics. Supporting factors include school support, learning flexibility, and effective collaboration between teachers and students. Meanwhile, challenges involve time constraints, variations in student abilities, and teachers' readiness to design differentiated instruction. The study concludes that talent-based projects have significant potential as an effective differentiated learning strategy for optimizing students' holistic development.